USING THE ADVOCACY COALITION FRAMEWORK TO REJECT THE ENVIRONMENTAL PERMIT FOR HAZARDOUS AND TOXIC WASTE PROCESSING: RESOURCES AND STRATEGY USED BY COMMUNITY OF LAKARDOWO VILLAGE - RAMADITYA RAHARDIAN; RIZKY WIJAYANTI; ANTUN MARDIYANTA (Universitas Muhammadiyah Yogyakarta, 2020)
This research aims to see how a set of policy advocacy carried out by a community of Penduduk Lakardowo Bangkit (Pendowo Bangkit) to reject the environtmental permit policy for Hazardous and Toxic Waste treatment in Lakardowo Village and close the waste company, which is considered to pollute the environment. Advocacy Coalition Framework (ACF) theory as the main analysis to observe the reality that occurs in the field that only sees resources in advocacy includes formal legal authorities to make a decision, develop a public opinion, information and data obtained, mobilize forces to carry out the pressure, finance, and the art of leadership. We use a qualitative research method with data collection techniques through in-depth interviews with several informants as well as digging documentation relating to the issue of policy advocacy occurred in Lakardowo Village. The number of informants in the research were four people, determined based on the purposive sampling technique. In checking the validity of the data, we use the triangulation of sources such as data reduction, data presentation, data condensation, drawing conclusions, and verification. The findings show that, in reality, the villagers through the Pendowo Bangkit community had used various resources and strategies in policy advocacy to reject the permit policy for Hazardous And Toxic Waste treatment in Lakardowo Village and demanded the closure of the industry. The results of the policy advocacy carried out have not succeeded in producing positive results in favor of the people of Lakardowo Village.